2007
DOI: 10.1080/00103620701378474
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Application of Biosolids on Apricot Production

Abstract: Abstract:The use and disposal of biosolids, or wastewater treatment sludge, as a fertilizer and soil amendment is becoming increasingly widespread. We evaluated the multiyear use of biosolids in apricot (Prunus armeniaca L.) production, grown on productive agricultural soils. Class A biosolids were initially applied annually at rates of 0, 1.9, 5.8, and 11.7 Mg . ha 21 (dry basis) to a 2-year-old apricot orchard on the USDA-ARS research site on the eastern side of the San Joaquin Valley, CA. These application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…The lowest value was TC and the highest value was T5. Schroeder et al (2008), in a field study with wheat (Triticum aestivum) and Bañuelos et al (2007), in a field study with apricot (Prunus armaniaca), found the same tendency in the CE regarding the application of biosolids. This situation could imply a risk of salinity for the soil.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The lowest value was TC and the highest value was T5. Schroeder et al (2008), in a field study with wheat (Triticum aestivum) and Bañuelos et al (2007), in a field study with apricot (Prunus armaniaca), found the same tendency in the CE regarding the application of biosolids. This situation could imply a risk of salinity for the soil.…”
Section: Resultsmentioning
confidence: 75%
“…El valor más bajo fue del TC y el valor más alto fue del T5. Schroeder et al (2008), en un estudio de campo con trigo (Triticum aestivum) y Bañuelos et al (2007), en un estudio de campo con chabacano (Prunus armaniaca), encontraron la misma tendencia en la CE respecto a la aplicación de biosólidos. Esta situación podría implicar un riesgo de salinidad para el suelo.…”
Section: Resultsunclassified
“…The macro- and micro-nutrient status of uninfected controls and Las-infected plants was assessed by assaying the concentrations of Ca, K, Mg, Fe, Cu, Mn, and Zn via Inductively-Coupled Plasma Optical Emission Spectroscopy (ICP-OES) in leaf tissues as previously described [74]. Briefly, the same ground leaf tissues used for proteomic analysis was oven-dried and 0.5 g was ashed at 510°C for 9 hrs, allowed to cool, and digested in 10 mL of 1 N HNO 3 for 1 h. The filtered supernatant was brought to volume (25 mL) and the intensities of atomic emissions at 396.847 nm for Ca, 766.491 nm for K, 279.553 nm for Mg, 238.204 nm for Fe, 327.395 nm for Cu, 257.610 nm for Mn, and 213.857 nm for Zn was measured on an ICP-OES System (Varian Vista Pro CCD Simultaneous ICP-OES attached to Varian SPS 5 Sampler Preparation System, Agilent, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The same samples used for proteomic analysis were assayed for major cationic elements, Ca, K, Mg, Fe, Cu, Mn, and Zn via Inductively-Coupled Plasma Optical Emission Spectroscopy (ICP-OES) as previously described [56]. Briefly, leaf tissues were oven-dried and 0.5g was ashed at 510 ° C for 9hrs, allowed to cool, and digested in 10 mL of 1N HNO 3 for 1 h. The filtered supernatant was brought to volume (25 mL) and the intensities of atomic emissions at 396.847nm for Ca, 766.491nm for K, 279.553nm for Mg, 238.204nm for Fe, 327.395nm for Cu, 257.610nm for Mn, and 213.857nm for Zn was measured on an ICP-OES System (Varian, Vista Pro CCD Simultaneous ICP-OES attached to Varian SPS 5 Sampler Preparation System, Agilent, USA).…”
Section: Methodsmentioning
confidence: 99%